Melatonin carbon dot-based hydrogel with antioxidant, antibacterial and osteogenesis-promoting functions as well as preparation method and application of melatonin carbon dot-based hydrogel

By combining melatonin carbon dots with biocompatible hydrogels to form an acid-responsive complex, the problems of long treatment time and insufficient local antibiotic delivery during traditional treatment of infectious bone injuries are solved, and early release is achieved Melanin and antibacterial significantly promote the repair efficiency of infectious bone injuries.

CN119113203APending Publication Date: 2024-12-13SUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411126592.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Traditional methods for treating infectious bone injury have problems such as long treatment time, insufficient local antibiotic delivery, insufficient autologous bone supply and risk of immune rejection, and it is difficult to effectively promote the repair of infectious bone injury.

Method used

Develop a melatonin carbon dot-based hydrogel with antioxidant, antibacterial and bone-promoting functions. Melatonin carbon dots are prepared by hydrothermal synthesis and combined with biocompatible hydrogels to form acids Responsive complexes, which can intelligently release melatonin to remove ROS and inhibit bacteria, promote bone repair.

Benefits of technology

The hydrogel realizes early release of melatonin at infectious bone injury, clears ROS, inhibits bacterial growth, improves bone repair environment, significantly shortens treatment time, improves bone repair efficiency, and has good biocompatibility and stability .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113203A_ABST
    Figure CN119113203A_ABST
Patent Text Reader

Abstract

The invention discloses melatonin carbon dot-based hydrogel with antioxidant, antibacterial and osteogenesis promoting functions as well as a preparation method and application of the melatonin carbon dot-based hydrogel, and belongs to the technical field of biomedical materials. The melatonin carbon dot-based hydrogel comprises an antioxidant, antibacterial and osteogenesis-promoting matrix and a matrix carrier, the antioxidant, antibacterial and osteogenesis-promoting matrix is melatonin carbon dots; and the matrix carrier is biocompatible hydrogel. Schiff base bonds are formed between the hydrogel and the melatonin carbon dots, so that the hydrogel can intelligently respond to the acidic microenvironment at the injured part of the infected bone and release a large number of melatonin carbon dots, excessive active oxygen in the microenvironment is removed in the early stage of implantation, and bacteria are quickly killed in multiple dimensions through the size effect and the charge effect of the hydrogel. In addition, due to continuous release of the melatonin carbon dots, long-acting bacteriostasis is achieved, the osteogenesis microenvironment is improved through anti-inflammation and anti-oxidation, and then bone injury repair is promoted. The hydrogel disclosed by the invention has a good application prospect in the field of treating infectious bone injury.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical materials, and in particular to a melatonin carbon dot-based hydrogel with antioxidant, antibacterial and osteogenic functions, and a preparation method and application thereof. Background Art

[0002] Infected bone injuries have long been a difficult problem in orthopedics. Infection can seriously damage the regenerative capacity of local tissues and bones, making it difficult for injuries to heal. The traditional standard treatment of infected bone injuries includes two main tasks, namely infection suppression and bone damage reconstruction. Infection suppression is the main part of treatment. Current clinical treatment methods include debridement of the infected site, systemic application of antibiotics, and implantation of antibiotic-impregnated spacers. However, due to vascular damage and bone necrosis caused by infection, it is difficult to achieve an effective dose of systemic antibiotics locally. Antibiotic-impregnated spacers can deliver antibiotics locally and promote bone grafting through membrane induction, but a second operation is required about 6 weeks after the first operation to remove the spacer. Only when the infection is controlled does the bone injury begin to enter the repair stage, and bone transplantation or bone transport technology is usually used to promote bone repair at the infected site. Although autologous bone is an effective bone implant, it faces problems such as insufficient donor bone volume and donor site complications. The treatment of allogeneic bone transplantation is also limited by its potential immune rejection and infection risks. Bone transport technology based on distraction osteogenesis is an effective bone reconstruction method, but its main disadvantage is that the treatment time is too long, which can reach more than 10 months. Traditional multi-stage treatment strategies have disadvantages such as long treatment time and burden on patients. Therefore, developing antibacterial and osteogenic biomaterials to treat infected bone injuries will be a therapeutic strategy with important clinical significance. Summary of the invention

[0003] Purpose of the invention: The purpose of the present invention is to provide a composite hydrogel loaded with multifunctional melatonin carbon dots and a preparation method thereof. The composite hydrogel has the characteristics of acid responsiveness and long release time, and can be used for biological tissue repair.

[0004] Technical solution: The present invention provides a melatonin carbon dot-based hydrogel with antioxidant, antibacterial and osteopromoting functions, wherein the melatonin carbon dot-based hydrogel comprises an antioxidant, antibacterial and osteopromoting matrix and a matrix carrier; the antioxidant, antibacterial and osteopromoting matrix is ​​melatonin carbon dots; and the matrix carrier is a biocompatible hydrogel.

[0005] Furthermore, the melatonin carbon dots are prepared by a hydrothermal synthesis method.

[0006] Furthermore, the melatonin carbon dots are solid nanoparticles with a particle size of 3-6 nm.

[0007] Furthermore, the biocompatible hydrogel is made of GelMA and oxidized hyaluronic acid.

[0008] Furthermore, the melatonin carbon dots are connected to the biocompatible hydrogel via Schiff base bonds.

[0009] The present invention also provides the use of the melatonin carbon dot-based hydrogel having antioxidant, antibacterial and osteogenic functions in biological tissue repair.

[0010] The present invention also provides a method for preparing the above melatonin carbon dot-based hydrogel.

[0011] S11, adding melatonin to deionized water, dispersing it uniformly by ultrasound, and then adding the mixture into a hydrothermal synthesis reactor, and heating it at 160-200° C. for 3-6 hours;

[0012] S12, after the heating is completed, the hydrothermal reactor is cooled and taken out, the supernatant is collected by filtering with a filter head, the supernatant is dialyzed with a dialysis bag with a molecular weight of 500 kDa, and finally freeze-dried with a freeze dryer to obtain melatonin carbon dots;

[0013] S13, adding hyaluronic acid to deionized water, stirring magnetically at room temperature until dissolved, then adding sodium periodate thereto, continuing magnetic stirring, and finally adding ethylene glycol to terminate the reaction; collecting the solution after the reaction and dialyzing it, and freeze-drying the liquid after the dialysis to obtain oxidized hyaluronic acid;

[0014] S14, mixing GelMA, a photoinitiator, the oxidized hyaluronic acid prepared in step S13 and deionized water, and placing the mixture in a water bath until it is completely dissolved to obtain an oxidized hyaluronic acid / GelMA composite hydrogel, i.e., a biocompatible hydrogel;

[0015] S15, mixing the melatonin carbon dots and the biocompatible hydrogel to obtain the melatonin carbon dots-based hydrogel.

[0016] Furthermore, in the oxidized hyaluronic acid / GelMA composite hydrogel, the concentration of GelMA is 5-10%, and the concentration of oxidized hyaluronic acid is 0.5-1%.

[0017] Furthermore, the photoinitiator is lithium phenyl-2,4,6-trimethylbenzoylphosphonate.

[0018] Furthermore, the concentration of melatonin carbon dots in the melatonin carbon dot-based hydrogel is 125-500 μg / mL.

[0019] The composite hydrogel loaded with multifunctional melatonin carbon dots prepared by the present invention has the characteristics of acid responsiveness and long release time. This is because a Schiff base bond is formed between the hydrogel and the melatonin carbon dots MCD, which can intelligently respond to the acidic microenvironment of the infected bone defect and release a large amount of MCD, thereby removing excessive ROS in the microenvironment in the early stage of implantation, and through its size effect and charge effect, inducing the production of a large amount of ROS inside the bacteria to kill bacteria rapidly in multiple dimensions. In addition, the sustained release of MCD not only achieves long-term antibacterial effect, but also improves the osteogenic microenvironment through anti-inflammatory and antioxidant effects, thereby promoting the repair of infectious bone damage.

[0020] Beneficial effects: Compared with the prior art, the present invention has the following outstanding advantages:

[0021] 1. The present invention prepares melatonin into melatonin carbon dots, and mixes the melatonin carbon dots into a hydrogel prepared from methacrylic anhydride gelatin and oxidized hyaluronic acid to obtain a composite hydrogel loaded with multifunctional melatonin carbon dots. When the melatonin carbon dots are dispersed in a hydrogel containing a large number of aldehyde groups in the molecular chain, the amino groups on the surface of these melatonin carbon dots will form Schiff base bonds with the aldehyde groups of the hydrogel, and this effect will increase the mechanical strength of the hydrogel. Also, due to the formation of Schiff base bonds between the hydrogel and the melatonin carbon dots, it can intelligently respond to the acidic microenvironment at the infected bone lesion, release a large number of melatonin carbon dots at an early stage, and promote the repair of infectious bone lesions.

[0022] 2. Melatonin carbon dots retain the antioxidant properties of melatonin and can effectively remove reactive oxygen free radicals produced by infectious bone damaged tissues to protect cells from ROS damage. At the same time, melatonin carbon dots can reduce the content of antioxidant enzymes in bacteria, making them unable to resist excessive ROS and thus die, which is beneficial to promote the repair of biological tissues.

[0023] 3. The hydrogel preparation method of the present invention is simple, and the prepared hydrogel has good stability. It can improve the high ROS microenvironment of infectious bone injury, kill bacteria in the microenvironment and has a good osteogenesis effect. It has good application prospects in the field of treating infectious bone injury. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 TEM image and particle size distribution of the MCD prepared in Example 1;

[0025] Figure 2 The XPS spectra of melatonin and MCD and the high-resolution XPS spectra of C1s, N1s and O1s in Example 1;

[0026] Figure 3 is the infrared absorption spectrum of melatonin and MCD in Example 1;

[0027] Figure 4The mechanical strength test of different hydrogels in Example 3;

[0028] Figure 5 The cross-sectional morphologies of different hydrogels prepared in Example 3 were photographed by SEM;

[0029] Figure 6 is the cumulative release of MCD in Example 3;

[0030] Figure 7 The skeleton staining images of BMSCs grown on different hydrogels in Example 3;

[0031] Figure 8 The fluorescence images of ROS in BMSCs induced by hydrogen peroxide after treatment with different hydrogels in Example 3;

[0032] Fig. 9 Bacterial plate counts and plate count quantification on different hydrogel surfaces in Example 3;

[0033] Fig.10 is the ability of different hydrogels in Example 3 to induce bacterial oxidative stress;

[0034] Fig.11 The images were generated for observing calcium nodules on the surface of BMSCs treated with different hydrogels by Alizarin Red staining in Example 3;

[0035] Fig.12 This is the gene expression heat map of BMSCs treated with GH-MCD hydrogel and GH hydrogel in Example 3;

[0036] Fig.13 This is the GSEA diagram of the genes related to Staphylococcus aureus infection regulated by GH-MCD hydrogel in Example 3;

[0037] Fig.14 This is a cell diagram of bacterial cell co-culture in Example 3;

[0038] Fig.15 This is a fluorescence image of ROS detection in the mouse skull defect in Example 4;

[0039] Fig.16 This is the residual bacteria plating experiment in the infected femoral condyle defect of the rat femoral condyle in Example 4;

[0040] Fig.17 The Micro-CT scan of rat femur (A) and quantitative analysis (B) in Example 4;

[0041] Fig.18 This is the H&E staining image of the rat femur in Example 4. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0043] Example 1 Preparation of melatonin carbon dots

[0044] This embodiment relates to a method for preparing melatonin carbon dots, which specifically comprises the following steps:

[0045] 0.2g melatonin was added to 10mL deionized water, and the mixture was evenly dispersed by ultrasound. Then the mixture was added to a 20mL hydrothermal synthesis reactor, and heated at 180°C for 4 hours. After the hydrothermal reactor was cooled, it was taken out, the supernatant was collected, and filtered with a 0.22μm filter head to remove large particles. The filtered solution was dialyzed for 24 hours using a dialysis bag with a molecular weight of 500Da. The dialyzed solution was freeze-dried using a freeze dryer to obtain (MCD). MCD was collected in a 50mL centrifuge tube and stored in a 4°C refrigerator for later use.

[0046] The melatonin carbon dots prepared above were characterized by transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectroscopy (FTIR). The relevant characterization and analysis results are as follows:

[0047] TEM results are as follows Figure 1 As shown in Figure 1, melatonin carbon dots are quasi-spherical with a lattice fringe structure, uniform particle size distribution, and a diameter of about 4 nm. The chemical structure and composition of melatonin carbon dots were analyzed by XPS. The results are shown in Figure 1. Figure 2 As shown in the figure, no new elements are generated after melatonin is prepared as MCD. The typical functional groups of melatonin are shown in the XPS high-resolution spectrum, such as CH, CN, N-CO, COC, etc. After being prepared as MCD, its structure changes and -NH2 is generated. The Fourier transform infrared spectrum also shows similar results. The results are shown in the figure. Figure 3 As shown in the figure, MCD contains a large number of functional groups that already exist in melatonin, such as -CH3 (1485.1 cm-1) and -NC=O (3305.1 cm-1), etc. However, MCD also produces some new functional groups, such as -OH (2565 cm-1), C≡C (2152.3 cm-1) and -NH2 (3408.5 cm-1), which is consistent with the results of XPS analysis.

[0048] Example 2 Preparation of oxidized hyaluronic acid

[0049] This embodiment relates to a method for preparing oxidized hyaluronic acid, which specifically comprises the following steps:

[0050] Weigh 1.5g of hyaluronic acid and add it to a clean beaker containing 150mL of deionized water. Stir magnetically at room temperature until dissolved, then add 802mg of sodium periodate, continue magnetic stirring for 2 hours, and then add 200μL of ethylene glycol to the beaker to terminate the reaction. Collect the solution after the reaction and dialyze for 48 hours, during which the deionized water is replaced every two hours. After the dialysis is completed, the liquid is freeze-dried using a freeze dryer to obtain oxidized hyaluronic acid (HA-CHO).

[0051] Example 3 Preparation and performance study of composite hydrogel loaded with multifunctional melatonin carbon dots

[0052] 3.1 Preparation method

[0053] Under light-proof conditions, 1 g of methacrylic anhydride gelatin (GelMA) was weighed and placed in a 50 mL centrifuge tube, 50 mg of photoinitiator (lithiumphenyl-2,4,6-trimethyl-benzoylphosphinate, LAP) and 100 mg of oxidized hyaluronic acid prepared in Example 2 were added thereto, and then 15 mL of deionized water was added, and the mixture was placed in a light-proof 37 ° C water bath until completely dissolved, and then a certain amount of deionized water was added to make the volume 20 mL to obtain 20 mL of GH hydrogel. Then 10 mg of melatonin carbon dots prepared in Example 1 were added to the GH hydrogel to obtain a composite hydrogel solution loaded with multifunctional melatonin carbon dots (the concentration of melatonin carbon dots in the GH hydrogel solution was 125-500 μg / mL). Then a blue light source with a wavelength of 405 nm was used for photocrosslinking for 1 min to obtain a solid composite hydrogel loaded with multifunctional melatonin carbon dots (GH-MCD).

[0054] According to the above preparation method, GH-MCD composite hydrogel solutions with melatonin carbon dots in the GH hydrogel solution at concentrations of 125, 250 and 500 μg / mL were prepared, respectively, and named GH-125MCD, GH-250MCD, and GH-500MCD for subsequent research.

[0055] 3.2 Performance Study

[0056] Taking the composite hydrogel loaded with multifunctional melatonin carbon dots prepared in 3.1 as an example, its structure, release characteristics, biocompatibility, antioxidant properties, antibacterial properties and effects on osteogenesis were studied.

[0057] 3.2.1. Mechanical properties of composite hydrogels and the effect of different pH values ​​on their structure

[0058] Cut off the head of the 5mL syringe with a blade, then pull out the piston, cut the piston tip flat with a blade as a mold for preparing the hydrogel, then draw 90μLGH and GH-MCD composite hydrogel solution into the mold, then crosslink with blue light for 1 minute to form gel, carefully push out the GH hydrogel and GH-MCD composite hydrogel after gelation, so that a cylindrical hydrogel sample with a diameter of 5mm and a height of 5mm is obtained. Prepare 4 GH hydrogels and GH-MCD composite hydrogels respectively. Place the prepared composite hydrogel sample on the platform of the universal mechanical testing machine, adjust the height of the compression platform to just contact the composite hydrogel, then reset all parameters, set the compression speed to 5mm / minute, start the mechanical compression test, and end the test when the mechanical curve shows a downward trend.

[0059] The GH hydrogel and GH-MCD composite hydrogel were immersed in PBS with pH 7.2 or pH 5.5 at 37°C for 24 hours, respectively, and then their compression modulus was tested by a universal mechanical testing machine; after alcohol gradient dehydration and critical point drying, their cross-sectional morphology was photographed by SEM.

[0060] The mechanical test results show that ( Figure 4 ), at pH 7.2, the compression modulus of GH-MCD composite hydrogel was 29.0±1.1kPa, which was greater than 25.2±1.5kPa of GH hydrogel. This was because more Schiff base bonds were formed between MCD and GH hydrogel, increasing its compression modulus. At pH 5.5, the compression modulus of GH-MCD composite hydrogel decreased significantly, even less than that of GH hydrogel, which was precisely because more Schiff base bonds were broken in GH-MCD composite hydrogel.

[0061] SEM results are as follows Figure 5 As shown in the figure, at pH 7.2, both GH hydrogel and GH-MCD composite hydrogel have loose macroporous structures. At pH 5.5, the macroporous structures of both GH hydrogel and GH-MCD hydrogel are destroyed, and the macroporous structure of GH-MCD composite hydrogel is destroyed more thoroughly, which is caused by the destruction of more Schiff base bonds in GH-MCD composite hydrogel.

[0062] 3.2.2. Release test

[0063] Four solid GH-MCD hydrogels prepared with 400 μL hydrogel solution were prepared as duplicate samples. The GH-MCD composite hydrogels were soaked in 4 mL of PBS at pH 7.2 and pH 5.5, respectively, and then placed in a 37 ° C oven for incubation. 1 mL of PBS was aspirated and collected into a 1.5 mL Ep tube at 2 hours, 1, 2, 3, 4, 5, 6, 7, 9, 11, 14, and 21 days, and then 1 mL of fresh PBS was added. Finally, the amount of released MCD was detected by UV-visible spectrophotometer. The standard curve of MCD was obtained by the following method: MCD was dissolved in PBS solution, and MCD was evenly distributed in the PBS solution by ultrasound to obtain MCD solutions with concentrations of 25, 50, 75, 100, 125, and 150 μg / mL, and then the absorption peaks corresponding to the above concentrations of MCD aqueous solutions were detected using a UV-visible spectrophotometer (baseline calibration was performed using PBS solution first), the absorption peaks at a wavelength of 310 nm were counted, and then a standard curve was drawn based on the relationship between the MCD concentration and the peak. The results are shown in Figure 1. Figure 6 As shown, the Schiff base bonds in the GH-MCD composite hydrogel can intelligently respond to the acidic microenvironment, and the MCD is released faster under acidic conditions.

[0064] 3.2.3. Biocompatibility test

[0065] In the clean bench, use a 0.22μm sterile filter to filter the prepared hydrogel solutions to remove bacteria, then draw 200μL of sterile hydrogel solutions from each group and add them to the sterilized syringe mold (cut off the head of the 5mL syringe with a blade, then pull out the piston, and cut the piston tip flat with a blade to serve as a mold for preparing hydrogels). Use a blue light source to irradiate the hydrogel solution for 1 minute to gel it. Each group of 3 hydrogels is used as a duplicate sample. After gelling, gently push it into a sterile 12-well plate, then wash it three times with sterile PBS to remove residual photoinitiator. Then put the prepared hydrogel at the bottom of the 24-well plate, and then add 1.5mL of 3×10 4 The cells were cultured in α-MEM complete culture medium (500 mL α-MEM complete culture medium consists of 450 mL α-MEM basal culture medium + 45 mL fetal bovine serum + 5 mL double antibody (penicillin-streptomycin)), and the effect of GH-MCD composite hydrogel on cell adhesion and spreading was observed by skeleton staining.

[0066] The results of skeleton staining are as follows Figure 7As shown, GH hydrogels exhibit good biocompatibility and are conducive to cell adhesion and spreading. The filopodia of BMSCs grown on the surface of each group of GH-MCD composite hydrogels are significantly more than those of GH hydrogels, and the cells grow well on the composite hydrogels with three MCD concentrations, indicating that the addition of MCD not only does not produce cytotoxicity, but also enhances the adhesion of cells to the composite hydrogel, proving that GH-MCD composite hydrogels have excellent biocompatibility.

[0067] 3.2.4. ROS removal test

[0068] Rat BMSCs (Bone mesenchymal stem cells) were placed at 3×10 4 Cells were inoculated in a 12-well plate and 1.5 mL of α-MEM complete medium was added. After 24 hours, α-MEM complete medium containing 100 μM H2O2 was replaced and incubated for another 12 hours. Then, each well was washed with sterile PBS to remove residual H2O2, and then new α-MEM complete medium was added. 200 μL of each group of hydrogels (GH, GH-125MCD, GH-250MCD, GH-500MCD) was clamped into the culture medium in the above-mentioned well plate with tweezers. No hydrogel was added to the Ctrl group (rat BMSC) and the H2O2 group (rat BMSC+H2O2). After continuing to cultivate for 24 hours, the BMSCs of each group were stained with a DCFH-DA staining kit (Biyuntian, item number S0033S), and the fluorescence images of each group were observed with an inverted fluorescence microscope.

[0069] The results are as follows Figure 8 As shown in the figure, compared with the normal Ctrl group, a large amount of ROS appeared inside the cells of the H2O2-induced group, while the ROS inside the cells of the H2O2+GH hydrogel group did not decrease, indicating that the GH hydrogel had no antioxidant effect. Even in the H2O2+GH-125MCD composite hydrogel group with the lowest MCD concentration, the ROS inside the cells also decreased significantly, indicating that the GH-MCD composite hydrogel has an excellent antioxidant effect and can protect cells from oxidative stress caused by H2O2.

[0070] 3.2.5. Antimicrobial test

[0071] 20 μL of 10 6CFU / mL of S. aureus suspension was added to the surface of each group of hydrogels (GH, GH-125MCD, GH-250MCD, GH-500MCD), and then the well plate was placed in an incubator in the bacterial room for 24 hours. After 24 hours, 1.5 mL of sterile PBS solution was added to each well of the well plate, and the S. aureus was resuspended by repeatedly blowing with a pipette, and then an appropriate amount of S. aureus suspension was evenly coated on the surface of the LB solid plate, and continued to be cultured for 18 to 24 hours, and then the colonies on the surface of the LB solid plate were counted by ImageJ software.

[0072] The results are as follows Fig. 9 As shown, after 24 hours, the number of surviving bacteria on the GH hydrogel hardly decreased, the bacterial survival rate on the GH-125MCD composite hydrogel was about 60%, the bacterial survival rate on the GH-250MCD composite hydrogel was about 25%, and the bacterial survival rate on the GH-500MCD composite hydrogel was the lowest, less than 10%.

[0073] 3.2.6. GH-MCD composite hydrogel regulates ROS in bacteria

[0074] S. aureus was added at 1×10 8 CFU / mL of bacteria were inoculated on the surface of each group of hydrogels, 1 mL of LB medium was added to each well, and the cells were placed in an incubator for 30 minutes. After that, the bacterial suspension was aspirated, centrifuged, and rinsed with sterile PBS three times. Then, DCFH-DA staining solution (final concentration was 10 μM) was added and incubated in a 37°C constant temperature shaker for 20 minutes away from light. Finally, the level of ROS in the bacteria was detected by a fluorescent microplate reader (excitation wavelength 488 nm).

[0075] The results are as follows Fig.10 As shown in the figure, as the concentration of melatonin carbon dots in the hydrogel increases, more ROS are produced in the bacteria, indicating that melatonin carbon dots-based hydrogel exerts its bactericidal effect by inducing bacterial oxidative stress.

[0076] 3.2.7. Osteogenesis performance test

[0077] Rat BMSCs were seeded in 12-well plates (3 × 10 4 Cells) were added to the wells and 1.5 mL of α-MEM complete medium was added. After 24 hours, the medium was replaced with rat osteogenic induction medium (1.5 mL of osteogenic induction medium was added to each well, and α-MEM complete medium was still added to the Ctrl group). 200 μL of hydrogels in each group (GH, GH-250MCD, GH-500MCD) were immersed in the above medium, and the medium was replaced every two days. Alizarin red staining was performed after 14 days.

[0078] Alizarin red staining results Fig.11 As shown in the figure, like the osteogenic induction group (cells were cultured with osteogenic induction medium only without adding hydrogel), only a small amount of calcium nodules were produced on the surface of BMSCs in the GH hydrogel-treated group, and the calcium nodules were small in size, indicating that the effect of GH hydrogel in promoting osteogenic differentiation was limited. However, a large number of calcium nodules were produced on the surface of BMSCs treated with GH-250MCD and GH-500MCD composite hydrogels, and the particles were large, indicating that GH-MCD composite hydrogels have a good long-term effect in promoting BMSC osteogenic differentiation, and the quantitative results of Alizarin Red are consistent with the results of Alizarin Red staining.

[0079] 3.2.8. In vitro validation of the effects on cell behavior and chondrogenic differentiation

[0080] Rat BMSCs were inoculated in a 6-well plate, and the medium was replaced with α-MEM complete medium after 24 hours. When the cells covered 70% of the well plate, the medium was replaced with osteogenic induction medium. At the same time, the prepared GH and GH-MCD composite hydrogels were added to the well plate. The medium was replaced every other day. After 5 days, the cells were lysed with Trizol reagent, and the samples were collected and sent to Hangzhou Lianchuan Biotechnology Co., Ltd. for subsequent sequencing and analysis.

[0081] Through bioinformatics analysis of the test results ( Fig.12 ), and found that there were many differentially expressed genes (DEGs) between the GH-MCD group and the GH group, and some genes expressed in the early stage of osteogenesis, such as Spp1 and Ibsp, were expressed at higher levels. GO and KEGG enrichment analysis of DEGs revealed that these differentially expressed genes were mainly related to inflammatory response, osteoclast differentiation, osteoblast differentiation, and complement and coagulation cascades. GH-MCD composite hydrogel significantly reduced its immunogenicity by downregulating immune system-related pathways, including hematopoietic cell lineage, complement and coagulation cascades, platelet activation, natural killer cell-mediated cytotoxicity, b-cell receptor signaling pathway, FcepsilonRI signaling pathway, and FcγR-mediated phagocytosis, providing a relatively stable microenvironment for bone regeneration.

[0082] RNA-Seq results also showed that genes related to Staphylococcus aureus infection were regulated ( Fig.13), that is, the gene expression of bacterial receptors and major complement on the cell surface is significantly reduced, which helps to reduce bacterial infection and inflammatory response and enhance the cell's defense against bacteria. In addition, GH-MCD composite hydrogel down-regulates the mTOR signaling pathway. The mTOR signaling pathway is related to autophagy and can reduce autophagosomes in cells. The GH-MCD composite hydrogel down-regulates the mTOR signaling pathway, so the number of autophagosomes in cells increases, which can then play a role in phagocytosis and killing intracellular bacteria, making cells less susceptible to repeated bacterial infection.

[0083] 3.2.9. Cell-bacteria co-culture

[0084] The 24-well plate with the hydrogel at the bottom was taken to the bacterial room and cultured at a ratio of cells: bacteria = 20:1 (cells, 1×10 5 Each well; bacteria, 5×10 3 Each well) was inoculated with BMSCs (DiO labeled, green fluorescence) and S. aureus (DiD labeled, red fluorescence), 1 mL of culture medium was added to each well (the culture medium consisted of 4 / 5 α-MEM complete medium and 1 / 5 LB medium), and then cultured in an incubator at 37°C, 5% CO2 for 24 hours. The plates were washed three times with sterile PBS containing double antibodies to remove extracellular bacteria, and then the BMSCs were digested with trypsin and re-seeded into a new 24-well plate. After 24 hours, an inverted fluorescence microscope was used for observation.

[0085] The results show that Fig.14 ), a large number of bacteria appeared inside the BMSCs treated with GH hydrogel, indicating that GH hydrogel could not help cells resist bacterial infection. However, there were basically no bacteria living inside the BMSCs treated with GH-MCD composite hydrogel, which showed that it helped cells to remove intracellular bacteria on the one hand, and enhanced the cells' resistance to bacterial infection on the other hand.

[0086] Example 4 Experimental study on GH-MCD composite hydrogel repairing infected bone lesions

[0087] (1) This experiment used C57 mice (8 weeks old, weighing about 20 g) to establish a skull infected bone defect model. Mice were from Zhao (Suzhou) New Drug Research Center Co., Ltd. The handling of experimental animals during the experiment was in accordance with the "Guiding Opinions on the Ethical Treatment of Laboratory Animals". The specific steps are as follows: The mice were randomly divided into 3 groups: S. aureus group (only S. aureus was added), GH group (GH hydrogel + S. aureus), GH-500MCD group (GH-500MCD hydrogel + S. aureus), 3 mice in each group. The mice were intraperitoneally injected with sodium pentobarbital. After they were deeply anesthetized, the hair on their heads was removed with a shaver. The skull skin was disinfected with iodine. The skin of the skull was cut open with a scalpel. Next, the skull membrane was cut open to expose the skull. A circular full-thickness bone defect with a diameter of 2.5 mm was formed with a drill. The defect areas of the mice in different groups were then filled with different types of hydrogel solutions. No hydrogel was added to the S. aureus group. A blue light source with a wavelength of 405 nm was then used for photocrosslinking for 1 minute, and then 10 μL of 10 4 CFU / mLS.aureus; finally, suture the wound layer by layer; disinfect the sutured wound with iodine disinfectant; place the modeled C57 mice on a heating pad until the mice regain consciousness.

[0088] 3 and 7 days after surgery, mice were anesthetized with isoflurane and ROSBrite TM 700 (in vivo imaging solution) was injected into the cranial area. Fluorescence images were acquired using an in vivo imaging system (PerkinElmer, Boston, USA). Fluorescence images were recorded to evaluate the production of ROS in the skull defect area of ​​mice.

[0089] The results show that Fig.15 ), on the third day of modeling, the fluorescence intensity of the skull defect in the S. aureus group and the GH group was extremely strong, indicating that a large amount of ROS was generated, while the fluorescence intensity of the GH-MCD group was greatly weakened. On the seventh day, a large amount of ROS still remained in the S. aureus group and the GH hydrogel group, while the fluorescence of the GH-MCD group was very weak, indicating that the ROS in the defect had been almost completely cleared, proving the good antioxidant effect of the GH-MCD composite hydrogel in vivo.

[0090] (2) Sprague-Dawley rats (8 weeks old, weighing 300-350 g) were used to establish a femoral condyle infected bone defect model. Rats were sourced from Zhao (Suzhou) New Drug Research Center Co., Ltd. The handling of experimental animals during the experiment was in accordance with the "Guiding Opinions on the Ethical Treatment of Experimental Animals". The specific steps are as follows: Sprague-Dawley rats were anesthetized intraperitoneally with sodium pentobarbital; after the Sprague-Dawley rats were deeply anesthetized, the hair at the femur was removed with a shaver; the skin of the femur was disinfected with iodine disinfectant; the skin at the femur was opened with surgical scissors, and the femoral condyle was exposed by blunt dissection with forceps; a bone defect with a diameter of 3 mm and a depth of 3 mm was formed with a drill bit, with 8 rats in each group, and models were created on both sides; 30 μL of the prepared GH and GH-MCD composite hydrogel solution before cross-linking was filled into the injury site, and then a blue light source with a wavelength of 405 nm was used for photocrosslinking for 1 minute, and then 10 μL of 10 7 CFU / mL S.aureus (in the control group, only S.aureus was dripped into the defect site without filling with hydrogel); finally, the wound was sutured layer by layer; the sutured wound was disinfected with iodine disinfectant; the Sprague-Dawley rats were placed on a heating pad until the rats regained consciousness. The rats were killed at 4 and 8 weeks after surgery, and the femur specimens were collected. The grouping was as follows: the S.aureus group (only S.aureus was added), GH group (GH hydrogel + S.aureus), and GH-MCD group (GH-500MCD composite hydrogel + S.aureus) were set up in the in vivo antibacterial experiment; the Ctrl group (pure defect group, no S.aureus), S.aureus group (only S.aureus was added), GH group (GH hydrogel + S.aureus), and GH-MCD group (GH-500MCD composite hydrogel + S.aureus) were set up in the in vivo bone repair experiment.

[0091] The femurs of rats were harvested 3 and 14 days after surgery. A certain amount of femurs were washed with sterile PBS and then plated for bacterial counting. The results showed that ( Fig.16 ), 3 days after surgery, the femur of the S. aureus group contained a large number of bacteria, and the GH group still contained a large number of bacteria, while the bacterial content in the GH-MCD group was significantly reduced. By 14 days, there were still many bacteria surviving in the S. aureus group and the GH group, while there were no bacteria remaining in the GH-MCD group, indicating that the GH-MCD composite hydrogel still has excellent antibacterial effects in vivo.

[0092] Rats were anesthetized with sodium pentobarbital at 4 and 8 weeks after surgery, and then femoral samples were removed. The femoral samples were immersed in formalin solution for 12 hours, then rinsed with PBS, and scanned and analyzed using Micro-CT.

[0093] Micro-CT scan of rat femur ( Fig.17 A) The results showed that the bone defect in the S. aureus group was more obvious than that in the Ctrl group, and some new bone tissue was produced in the GH group, indicating that the filled GH hydrogel has a certain ability to repair infectious bone damage. This may be because the filling of the GH hydrogel provides a bridge for signal exchange and nutrient delivery between cells at the defect end, thus having a certain bone repair effect. The GH-MCD composite hydrogel group showed a significant bone repair effect. Quantitative analysis results showed ( Fig.17 B), 4 weeks after surgery, the bone volume percentage (BV / TV) of the GH-MCD composite hydrogel group reached about 25%, and the trabecular thickness and trabecular number (Tb.Th and Tb.N) were significantly higher than those of the S.aureus group and the Ctrl group, while the trabecular separation (Tb.Sp) was the lowest. At 8 weeks, the new bone tissue almost completely covered the defect site, the new bone tissue deep in the bone defect was perfectly integrated with the surrounding bone tissue, and the bone surface was almost completely repaired.

[0094] Clean the femur specimens with PBS, place each two legs in a 50mL centrifuge tube, add 45mL of 14% EDTA decalcification solution, and shake on a shaker. Change the decalcification solution every day for a total of 30 days. Dehydrate the specimens and embed them in paraffin after 30 days. Steps: First, dehydrate the decalcified femur specimens with 70%, 85%, 95% and 100% ethanol, and soak the dehydrated femur in n-butanol overnight. Finally, wax the femur specimens, embed them, and slice them with a paraffin slicer. After slicing, stain the femur specimens with hematoxylin & eosin (H&E).

[0095] H&E staining results ( Fig.18 ) was consistent with the results of Micro-CT. At 4 weeks, the Ctrl group and the S. aureus group still had obvious cavities, the GH group had reduced cavities, and the GH-MCD group had significantly reduced cavities, with a large amount of new bone tissue generated. At 8 weeks, the new bone tissue structure of the GH-MCD group was more complete. This indicates that the GH-MCD composite hydrogel can promote bone formation and bone maturation.

[0096] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A melatonin carbon dot-based hydrogel with antioxidant, antibacterial and osteogenic functions, characterized in that: The melatonin carbon dot-based hydrogel comprises an antioxidant, antibacterial and osteogenic matrix and a matrix carrier; the antioxidant, antibacterial and osteogenic matrix is ​​melatonin carbon dots; and the matrix carrier is a biocompatible hydrogel.

2. The melatonin carbon dot-based hydrogel with antioxidant, antibacterial and osteogenic functions according to claim 1, characterized in that: The melatonin carbon dots are prepared by a hydrothermal synthesis method.

3. The melatonin carbon dot-based hydrogel with antioxidant, antibacterial and osteogenic functions according to claim 1, characterized in that: The melatonin carbon dots are solid nanoparticles with a particle size of 3-6 nm.

4. The melatonin carbon dot-based hydrogel with antioxidant, antibacterial and osteogenic functions according to claim 1, characterized in that: The biocompatible hydrogel is made of GelMA and oxidized hyaluronic acid.

5. The melatonin carbon dot-based hydrogel with antioxidant, antibacterial and osteogenic functions according to claim 1, characterized in that: The melatonin carbon dots are connected to the biocompatible hydrogel via Schiff base bonds.

6. Use of the melatonin carbon dot-based hydrogel having antioxidant, antibacterial and osteogenic functions according to any one of claims 1 to 5 in biological tissue repair.

7. A method for preparing the melatonin carbon dot-based hydrogel according to claim 1, characterized in that: The following steps are involved: S11, adding melatonin to deionized water, dispersing it uniformly by ultrasound, and then adding the mixture into a hydrothermal synthesis reactor, and heating it at 160-200° C. for 3-6 hours; S12, after the heating is completed, the hydrothermal reactor is cooled and taken out, the supernatant is collected by filtering with a filter head, the supernatant is dialyzed with a dialysis bag with a molecular weight of 500 kDa, and finally freeze-dried with a freeze dryer to obtain melatonin carbon dots; S13, adding hyaluronic acid to deionized water, stirring magnetically at room temperature until dissolved, then adding sodium periodate thereto, continuing magnetic stirring, and finally adding ethylene glycol to terminate the reaction; collecting the solution after the reaction and dialyzing it, and freeze-drying the liquid after the dialysis to obtain oxidized hyaluronic acid; S14, mixing GelMA, a photoinitiator, the oxidized hyaluronic acid prepared in step S13 and deionized water, and placing the mixture in a water bath until it is completely dissolved to obtain an oxidized hyaluronic acid / GelMA composite hydrogel, i.e., a biocompatible hydrogel; S15, mixing the melatonin carbon dots and the biocompatible hydrogel to obtain the melatonin carbon dots-based hydrogel.

8. The method for preparing melatonin carbon dot-based hydrogel according to claim 7, characterized in that: The concentration of GelMA in the oxidized hyaluronic acid / GelMA composite hydrogel is 5-10%, and the concentration of oxidized hyaluronic acid is 0.5-1%.

9. The method for preparing melatonin carbon dot-based hydrogel according to claim 7, characterized in that: The photoinitiator is lithium phenyl-2,4,6-trimethylbenzoylphosphonate.

10. The method for preparing melatonin carbon dot-based hydrogel according to claim 7, characterized in that: The concentration of melatonin carbon dots in the melatonin carbon dot-based hydrogel is 125-500 μg / mL.